The relationship between baby massage and baby sleep quality at the Sion Clinic - Sihombing, Juliana Sion; Lubis, Nur Azizah; Naimah Nasution (Institute Of Computer Science (IOCS), 2024)
The aim of this research is to see the relationship between oil massage performed on babies and their sleep quality. The type of research carried out was quasi-experimental with a pretest posttest one group design approach. Research was proposed to determine the relationship between baby massage and the quality of baby sleep. The population in this study was all babies aged 0-6 months who received massage for 2 weeks. The sample used used a total sampling technique so that the number of respondents used was the same as the population, namely 30 samples. The research results obtained an average pre-test score or mean of 1.40, while for the post-test score the average sleep quality score was 2.57. Because the average sleep quality score on the pre-test is < that of the post-test, this means there is a difference in the average sleep quality of the pre-test and post-test. The table above shows that the significant number (0.000) is much lower than the significant standard of 0.05, meaning there is an influence of massage on the sleep quality of babies aged 1-6 months.